Diet supplementation - Frączek, Małgorzata; Szumiło, Michał; Burdan, Franciszek; Szumiło, Justyna (Polish Journal of Public Health, 2012)
Diet supplementation is defined as individual supply of normal diet by condensed source of vitamins, minerals or other substances known as having nutritional or other physiological effect. Consumption of diet supplements has considerably increased in Poland and now they become an important group of over-the-counter specifics. Vitamins and minerals supplementation protects against their deficiency. But medical plants present in some supplements display various beneficial effects on the organism, including chemopreventive action against malignancies and cardio-vascular system diseases. However, administration of the supplements may be also associated with their overdose, interaction with other drugs and false results of some laboratory tests. Furthermore, plant stock used for production of supplements may be contaminated by some pathogenic microorganisms, mycotoxins or pesticides. Therefore, diet supplements have to be applied with caution based on the own health status.